PENGARUH INTENSITAS MODAL, MEKANISME CORPORATE GOVERNANCE, DAN PROFITABILITAS TERHADAP TAX AVOIDANCE PADA PERUSAHAAN PERBANKAN - Anisa Wantifa Pratiwi; Yuli Chomsatu (FINANSIA : Jurnal Akuntansi dan Perbankan Syariah, 2022)
This study aims to analyze the influence of capital intensity, corporate governance mechanisms, profitability on tax avoidance. In this study, the type of data used was quantitative data with the population of banking companies listed on the Indonesia Stock Exchange in 2015-2019. The determination of the sample was carried out using the purposive sampling method so that nine companies were obtained that met the criteria for five years. The data analysis method used is multiple linear regression. Based on the results of the analysis, it can be concluded that capital intensity affects tax avoidance, while the mechanism of corporate governance and profitability does not affect tax avoidance.